Touristification processes of memorials in Latin America; opportunity or threat to reparation? An analysis of individual cases - 1990-2020 (2022)
In the last three decades, there has been a significant increase in touristification processes in places of remembrance, with growing, although not homogeneous, impacts on a just social and spatial reparation. Regarding this, in this article it is maintained that the nature and intensity of the touristic impact depends on how the memorials are manifested. According to what has been studied, there are three modalities to creating them, distinguished by the place where they are built, their formal characteristics, and who promotes and administers them. To develop this thesis, two Latin-American memorials were studied from each of the modalities. These were selected for constituting paradigmatic and generalizable cases. The results show, on the one hand, that tourism has become a key factor in increasing interest in, and the numbers of visitors to, memorials and with that it is contributing to victim reparations and the recovery of spaces. However, on the other hand, under certain conditions, the touristic incursion can trigger disturbingprocesses for memory, the reparation to victims and the place of remembrance. The impacts range from trivialising to hiding, from museumizing to spectacularizing, and even reaching theintentional use of tourism as a way to whitewash traumatized territories, both in terms of memory as well as reparation.